Differences in team situational efficacy indicators in group phase of U-17 world football championship in Chile - Mikulic, I.; Barisic, V.; Basic, D. (Acta Kinesiologica, 2016)
The goal of this research is to establish differences in situational efficacy indicators between teams who passed the group phase of U-17 World football championship in Chile and those who did not. Situational efficacy indicators used in analysis were downloaded from FIFA's official website. Analyzed were the differences in 12 variables between teams who passed the group phase of championship and those who did not. T-test and Mann-Whitney test results showed that teams who passes and those who did not had a significant difference in these variables: ball possession (p=0.016), goals given (p=0.016) and goals received (p=0.001). Also, based on the results we established that these variables did not differ between teams who passed and those who did not: goal kicks (p=0.544), kicks within frame (p=0.241), kicks outside of frame (p=0.442), corner kicks (p=0.749), free kicks (p=0.676), offside (p=0.053), fouls (p=0.789), yellow card (p=0.101) and red card (p>0.5).